Higher prevalence of left ventricular hypertrophy in two Māori cohorts: findings from the Hauora Manawa/Community Heart Study. (5th January 2015) - Whalley, Gillian A.; Pitama, Suzanne; Troughton, Richard W.; Doughty, Rob N.; Gamble, Greg D.; Gillies, Tawhirimatea; Wells, J. Elisabeth; Faatoese, Allamanda; Huria, Tania; Richards, Mark; Cameron, Vicky A.
Abstract Objectives: Cardiovascular disease (CVD) is the leading cause of mortality in New Zealand with a disproportionate burden of disease in the Māori population. The Hauora Manawa Project investigated the prevalence of cardiovascular risk factors and CVD in randomly selected Māori and non‐Māori participants. This paper reports the prevalence of structural changes in the heart. Methods: A total of 252 rural Māori, 243 urban Māori; and 256 urban non‐Māori underwent echocardiography to assess cardiac structure and function. Multivariable logistic regression was used to determine variables associated with heart size. Results: Left ventricular (LV) mass measurements were largest in the rural Māori cohort (183.5, sd 61.4), intermediate in the urban Māori cohort (169.7, sd 57.1) and smallest in the non‐Māori cohort (152.6, sd 46.7; p<0.001). Similar patterns were observed for other measurements and indexation had no impact. One‐third (32.3%) met the gender‐based ASE criteria for LV hypertrophy (LVH) with higher prevalence in both Maori cohorts (highest in the rural cohort). There were three significant predictors of LVH: rural Māori (p=0.0001); age (p<0.0001); and gender (p=0.0048). Conclusion: Structural and functional heart abnormalities are more prevalent in Māori compared to non‐Māori, and especially rural Māori. Early identification should lead to better management, ultimately improving life expectancy and quality of life.